Functional synthetic polymers - Fink, Johannes Karl (John Wiley & Sons, Inc. ; Scrivener Publishing, LLC, 2019)
The text focuses on the basic issues and also the literature of the past decade. The book provides a broad overview of functional synthetic polymers. Special issues in the text are: Surface functionalization supramolecular polymers, shape memory polymers, foldable polymers, functionalized biopolymers, supercapacitors, photovoltaic issues, lithography, cleaning methods, such as recovery of gold ions olefin/paraffin, separation by polymeric membranes, ultrafiltration membranes, and other related topics.
Keywords: Polymers.; Polymeric composites.; elektronické knihy; electronic books